The Handbook of Nanomedicine - Jain, Kewal K. (Humana Press : Imprint: Humana, 2008)
Nanomedicine is clinical medicine with the application of nanobiotechnology, which is currently being used to research the pathomechanism of disease, refine molecular diagnostics, and aid in the discovery, development and delivery of drugs. In The Handbook of Nanomedicine, Prof. Kewal K. Jain distills the voluminous literature relevant to the subject into one concise, comprehensive and easy-to-use guide. Beginning with the basics, the subject is developed to potential clinical applications, many of which are still at an experimental stage. Important components of nanomedicine such as nanodiagnostics and nanopharmaceuticals are covered extensively. As this text is aimed at nonmedical scientists, pharmaceutical personnel, as well as physicians, descriptions of the technology involved and other medical terminology are kept as clear and simple as possible. In depth and cutting-edge, The Handbook of Nanomedicine informs its readers of the ever-growing field of nanomedicine, destined to play a significant role in the future of healthcare.